MATERIAIS AUDIOVISUAIS DIDÁTICOS E EDUCAÇÃO SEXUAL NA ESCOLA: UMA PESQUISA NOS ACERVOS VIDEOGRÁFICOS DO MINISTÉRIO DA EDUCAÇÃO E CULTURA E MINISTÉRIO DA SAÚDE DO GOVERNO BRASILEIRO - Vagner Matias do Prado; Arilda Inês Miranda Ribeiro; Luciana Cristine Fazano (Universidade do Oeste Paulista, 2011)
This article discusses sex differences as a research issue. It starts from the assumption that the work on sex education in schools should be effected beyond the biological dimension, focusing on the historical, cultural, social and political aspects that underlie the issue and influence the construction of cultural identities. In this manner, teaching support materials to implement these interventions are very important for the educational work, among them, the audiovisual materials are very productive. The proposed goal was to conduct a survey of educational videos with the Departments of Education, Culture and Health of the Brazilian Government in order to make a list containing titles of materials that could subsidize the pedagogical action. The measured results show a timid government initiative for the production of these materials, even sexuality shaping up as a crosscutting theme to be included as a school subject.